Alpha-SNAP (M105I) mutation promotes neuronal differentiation of neural stem/progenitor cells through overactivation of AMPK - Bustamante-Barrientos, Felipe A.; Méndez-Ruette, Maxs; Molina, Luis; Koning, Tania; Ehrenfeld, Pamela; González, Carlos B.; Wyneken, Ursula; Henzi, Roberto; Bátiz, Luis Federico (Frontiers in Cell and Developmental Biology, 2023)
The M105I point mutation in alpha-SNAP (Soluble N-ethylmaleimide-sensitive factor attachment protein-alpha) leads in mice to a complex phenotype known as hyh (hydrocephalus with hop gait), characterized by cortical malformation and hydrocephalus, among other neuropathological features. Studies performed by our laboratory and others support that hyh phenotype is triggered by a primary alteration in embryonic neural stem/progenitor cells (NSPCs) that leads to a disruption of the ventricular and subventricular zones (VZ/SVZ) during the neurogenic period. Besides the canonical role of alpha-SNAP in SNARE-mediated intracellular membrane fusion dynamics, it also negatively modulates AMP-activated protein kinase (AMPK) activity. AMPK is a conserved metabolic sensor that has been associated with the proliferation/differentiation balance in NSPCs. Here, we report that NSPCs from hyh mice (hyh-NSPCs) display increased levels of phosphorylated AMPK-alpha (pAMPKalphaThr172), which is associated with a preferential commitment with the neuronal lineage. Interestingly, pharmacological inhibition of AMPK completely abolished the increased generation of neurons in hyh-NSPCs, while the overactivation of AMPK increases neuronal differentiation in WT-NSPCs. Our findings support that -SNAP participates in regulating AMPK signaling in NSPCs, further modulating their neurogenic capacity. The naturally occurring M105I mutation of -SNAP provokes an AMPK overactivation in NSPCs, thus connecting the -SNAP/AMPK axis with the etiopathogenesis and neuropathology of the hyh phenotype.